Optimization of the Performance of the Demak Police Detective Unit to Improve the Handling of Online Fraud Crimes - Manurung, Hewith (Advances in Police Science Research Journal, 2024)
This writing is motivated by the large number of online fraud complaints that enter the Demak Police Satreskirm whose handling has not been maximized so that there is a buildup every year. The existence of this phenomenon is a form of subject performance that has not been optimal in carrying out treatment of existing audans. This paper aims to know, analyze and describe the optimization of the performance of the Demak Police Crime Squad Tipidter Unit to improve the handling of online fraud crimes. This writing uses a qualitative approach, uses primary and secondary data sources and takes place in Demak Regency. Data analysis is carried out by data reduction, data presentation, and conclusions. Data collection techniques use interviews, observation and document review techniques. The concepts used are the concept of handling online fraud crimes, the concept of Tipidter Units, as many theories used as performance theory, competence, infrastructure management and SWOT. The results showed that there is no special competence possessed by the Tipidter Unit to handle online fraud crimes and the facilities and infrastructure owned and used for handling online fraud crimes mostly belong to members and not belong to the Demak Regional Police. Based on the results of the study, problem solving was provided to optimize the performance of the Tipidter Unit to deal with online fraud crimes.